LEVEL OF PHYSICAL ACTIVITY AND ACADEMIC STRESS PERCEIVED BY NURSING STUDENTS DURING THE EXAM PERIOD - BRAVO, VERÓNICA TOMASA CAJAS (2024)
ACADEMIC STRESS IS A COMMON PROBLEM AMONG NURSING STUDENTS, ESPECIALLY DURING EXAM PERIODS. THIS STUDY AIMS TO ANALYZE THE RELATIONSHIP BETWEEN PHYSICAL ACTIVITY LEVELS AND PERCEIVED ACADEMIC STRESS IN NURSING STUDENTS DURING FINAL EXAMS. A DESCRIPTIVE CROSS-SECTIONAL STUDY WAS CONDUCTED WITH 43 STUDENTS. PHYSICAL ACTIVITY WAS MEASURED USING ACTIGRAPH WGT3X ACCELEROMETERS, AND ACADEMIC STRESS WAS ASSESSED WITH THE SISCO INVENTORY. DESCRIPTIVE STATISTICS AND NONPARAMETRIC TESTS (MANN-WHITNEY AND KRUSKAL-WALLIS) WERE USED TO ANALYZE THE DATA. RESULTS SHOWED THAT WOMEN REPORTED SIGNIFICANTLY HIGHER LEVELS OF ACADEMIC STRESS (P=.0049) AND THAT STUDENTS WITH HIGHER ACADEMIC WORKLOADS PERFORMED LESS MODERATE TO VIGOROUS PHYSICAL ACTIVITY (P<.05). SEDENTARY BEHAVIOR WAS HIGHER IN THOSE WITH LOWER STRESS LEVELS (P=.0492). THESE FINDINGS SUGGEST THAT ACADEMIC STRESS MAY NEGATIVELY INFLUENCE PHYSICAL ACTIVITY LEVELS, ESPECIALLY DURING PERIODS OF HIGH ACADEMIC DEMAND. IT IS RECOMMENDED THAT PROGRAMS THAT PROMOTE BOTH PHYSICAL ACTIVITY AND STRESS MANAGEMENT BE IMPLEMENTED IN UNIVERSITY ENVIRONMENTS TO IMPROVE STUDENT WELL-BEING. © 2024 FEDERACION ESPANOLA DE DOCENTES DE EDUCACION FISICA. ALL RIGHTS RESERVED.